Serosal membrane tuberculosis in Iran: A comprehensive review of evidences. (May 2023) - Ebrahimzadeh, Azadeh; Pagheh, Abdol Sattar; Mousavi, Tahoora; Fathi, Maryam; Moghaddam, Sayyed Gholamreza Mortazavi
Abstract: Tuberculosis (TB) is among the most common cause of serositis. There are many uncertainties in diagnostic and therapeutic approach to serous membranes tuberculosis. Our aim in the present review is to discuss the regional facilities for timely diagnosis, rapid decision-making and appropriate treatment regarding to serous membranes tuberculosis; with emphasis on situation in Iran. A comprehensive literature searches about the status of serous membranes tuberculosis in Iran were performed in English databases including Google Scholar, Science Direct, Scopus, Pub Med, and Web of Sciences, Persian SID databases, between 2000 and 2021. The main findings of the present review are as follow: a) pleural tuberculosis is more common than pericardial or peritoneal tuberculosis. b) Clinical manifestations are non-specific and so non-diagnostic. c) Smear and culture, PCR and characteristic granulomatous reaction have been used for definitive TB diagnosis by physicians. d) With Adenosine Deaminase Assays and Interferon-Gamma Release Assays in mononuclear dominant fluid, a possible diagnosis of TB is proposed by experienced physicians in Iran. e) In area of endemic for tuberculosis including Iran, a possible diagnosis of TB is enough to begin empirical treatment. f) In patients with uncomplicated tuberculosis serositis, treatment is similar to pulmonary tuberculosis. First line drugs are prescribed unless evidence of MDR-TB is detected. g) The prevalence of drug resistant tuberculosis (MDR-TB) in Iran is between 1% and 6%, and are treated by empirical standardized treatment. h) It is not known whether adjuvant corticosteroids are effective in preventing long term complication. i) Surgery may be recommended for MDR-TB. Tamponade or constrictive pericarditis and intestinal obstruction. In conclusion, it is recommended to consider serosal tuberculosis in patients who have unknown mononuclear dominant effusion and prolonged constitutional symptoms. Experimental treatment with first line anti-TB drugs can be started based on possible diagnostic findings.